Sveti Frančišek Asiški kot mirotvorec nekoč in danes - Šegula, Andrej (Bogoslovni vestnik, 2025)
Saint Francis of Assisi, through his life and writings, became a model of peace, reconciliation, and fraternity. His choice to live a simple, poor, and non-violent life was rooted in the Gospel call to love God and one’s neighbour. His encounter with Sultan al-Malik al-Kamil in 1219 stands as a powerful symbol of courageous interreligious dialogue. The spirit of peace that permeates Francis’s writings continues to inspire forgiveness, love, and brotherhood. In 1986, Pope John Paul II convened a historic interfaith prayer for peace in Assisi, which significantly advanced interreligious dialogue and has since become a lasting initiative. Pope Francis carries forward this vision in his encyclicals “La-udato si’” and “Fratelli tutti”, emphasizing peace, care for creation, and universal fraternity. Today, the Franciscan spirit resonates in Church documents, prayer initiatives, and ongoing efforts for peace and dialogue.
Keywords: Assisi 1986; bratstvo; Frančišek Asiški; Fratelli tutti; fraternity; interreligious dialogue; medverski dialog; mir; peace